Hubungan Status Sosial Ekonomi Orang Tua Dan Prestasi Belajar Siswa Pada Pembelajaran Matematika - Hirna Kentjana Sari (LPPM Politeknik Pratama, 2023)
This research aims to present a review of literature studies that examine the relationship between parents' socioeconomic status and students' learning achievement in the context of mathematics learning. This literature study was conducted to identify and understand the role of socioeconomic status in influencing students' mathematics learning achievement. Data for this study was obtained through a search of relevant scientific literature that included articles, journals, books and previous research that has been conducted in this area. The results of this literature study indicate that parental socioeconomic status has a significant influence on students' learning achievement in mathematics. Factors such as access to educational resources, access to additional educational opportunities, parental support, home environment, students' psychological well-being and school culture all play a role in this relationship. The research also highlights the importance of developing inclusive and equitable educational strategies to address inequalities in mathematics achievement between students from different socioeconomic backgrounds. Teachers and schools have a central role in creating a learning environment that supports all students, regardless of their socioeconomic background. This literature study provides a deeper understanding of the complex relationship between parental socioeconomic status and student learning achievement in mathematics. As such, this research provides an important foundation for further development in addressing educational inequalities and improving mathematics learning achievement of students from diverse socioeconomic backgrounds.